STUDI TENTANG LOKASI BENTENG-BENTENG DI SURAKARTA (1672, 1743, 1756, 1832) - Bimo Hernowo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2015)
Title: Study on the Location of Surakarta's Forts (1672, 1743, 1756, 1832) The Fortress in Surakarta (Vastenburg) was established in 1745 (Soedarmono, Kusumastuti, 2002). Some documents mention that the fort was built in 1743 referring to it as the De Grootmoedigheid (De VOC Site, 2015).The purpose of this paper is to discuss the possibility that there might be some other fortresses in Surakarta. This argument is based on descriptions given by William Barrington D'Almeida in Java documented in his book Live in Java: with Sketches of the Javanese, Vol. II in 1864 in which it is stated that a fort was established in Surakarta in 1672, that was built based on Vauban and Descartes design ideas. There is further evidence: A map of